Prevalence of survival without major morbidity and associated risk factors among very preterm infants: a systematic review and meta-analysis - Zhang, Xiangtong; Wang, Peiqin; Wan, Zhi; Xiong, Ping; Rao, Dandan; Yu, Zhangbin; Wu, Genfeng (Frontiers in Pediatrics, 2025)
IntroductionSurvival without major morbidity (SWMM) in very preterm infants represents a critical outcome measure in neonatal care. This systematic review evaluates both the prevalence of SWMM among infants born before 32 weeks' gestation and the associated risk factors.MethodsWe conducted a comprehensive search of PubMed, Web of Science, Embase, Cochrane Library, Scopus, CNKI, CBM, and Wanfang databases from inception through February 4, 2025. Two independent reviewers performed study selection and data extraction. Study quality was assessed using the Agency for Healthcare Research and Quality (AHRQ) checklist for cross-sectional studies and the Newcastle-Ottawa Scale (NOS) for cohort studies. Pooled prevalence was calculated using a random-effects model. Heterogeneity was explored through subgroup analyses and meta-regression, and publication bias was assessed via funnel plots and further evaluated with trim-and-fill analysis. Risk factors were evaluated using multivariate meta-analysis of adjusted odds ratios (ORs) with 95% confidence intervals (CIs).ResultsFrom 1,606 screened articles, 35 studies spanning twelve countries met inclusion criteria. The pooled SWMM incidence was 47% (95% CI: 40%–54%), with notable gestational age stratification: 67% (95% CI: 62%–72%) for infants <32 weeks vs. 44% (95% CI: 26%–61%) for those <28 weeks. Meta-analysis identified gestational age maturity (OR: 1.65; 95% CI: 1.50–1.81), antenatal corticosteroid administration (OR: 1.46; 95% CI: 1.12–1.89), and higher 5-minute Apgar scores (OR: 1.21; 95% CI: 1.06–1.37) as positive predictors of SWMM. Conversely, male sex (OR: 0.62; 95% CI: 0.55–0.71) and hemodynamically significant patent ductus arteriosus (OR: 0.51; 95% CI: 0.38–0.69) showed negative associations with SWMM.ConclusionThe review reports a 47% SWMM rate among very preterm infants, with higher rates observed in infants of later gestational age. Key predictors include gestational age, 5-minute Apgar score, and antenatal corticosteroids, while male sex and patent ductus arteriosus are associated with reduced SWMM. Limitations include heterogeneity in SWMM definitions and geographic variability. Future research should focus on standardizing outcome measures and validating risk factors through multinational studies.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025641924, PROSPERO CRD42025641924.